(3GdehVM dePGgH GdbQGA aj GMcGe GdaJM hGdEeGdIs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s ((3LYaQ Hf GHQGgje Hf LYaQ GdebQi GdSfghQi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMeO ddg GdYGde HNajGJ GdSQGFQ gPG cJGH GPcQ ajg Ef TGA Gddg JYGdi ePGgH GdbQG GdSHYI QMege Gddg ai GdaJM hGdEeGdI s
(3BNQgG (B:s
(3bGd CHh YeQh hbO GJjfG ai cJGHfG gPG Ydi LejY eG GaQOfGg Hg ef GNJdGa GdbQCI hePGgHge ai GdaJM hGdGeGdI Je cJGH GdehVM dePGgH GdbQG hGNJdGage ai GdaJM hGdEeGdI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs